Eupelops acromios - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Eupelops acromios (Hermann, 1804) Material – Two specimens in Çiftlik Village, Tekçam Area, Taşköprü forest, N 41° 14′ 39.56′′, E 34° 12′ 19.57′′, alt. = 1422 m, 15 May 2018, tree bark and debris of P. nigra. Previous record in Turkey – Konya (Dik et al. 1999). Global distribution – Semicosmopolitan. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 263, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Eupelops acromios; Arthropoda; Arachnida; Animalia; Eupelops; Biodiversity; Sarcoptiformes; Phenopelopidae; Taxonomy; 15. Life on land